Association between the growth arrest-specific 6 (Gas6) gene polymorphism c.834+7G > A and preeclampsia - BİNGÖL ÖZAKPINAR, ÖZLEM; TETİK, ŞERMİN (TAYLOR & FRANCIS LTD, 2016)
Objective: Preeclampsia (PE) is a hypertensive disease of pregnancy complicating 2-8% of all pregnancies. The exact pathophysiology still remains unknown. Growth arrest-specific 6 (Gas6) is a member of the vitamin K-dependent protein family and it has been suggested as a novel atherothrombotic risk factor with anti-angiogenic and pro-atherogenic properties. The goal of the our study was to investigate the relationships between the c.834+7G>A polymorphism of GAS6, plasma Gas6 levels and PE.Methods: A total of 150 women, including 82 preeclamptic pregnant women and 68 normotensive pregnant (NP) women, were recruited in the current study. Blood samples were taken from all participitants. Plasma Gas6 levels measured by an enzyme-linked immunosorbent assay. GAS6 polymorphism was determined using a PCR-RFLP method.Results: The plasma Gas6 levels of preeclamptic patients were significantly lower than those of NP women (8.653.70ng/ml and 10.89 +/- 4.23ng/ml respectively, p<0.001). The GG genotype was the most prevalent, and the risk of PE was 3.5-fold higher in pregnant women with GG genotype compared to woman with AA genotype (p<0.01). The A allele was less frequent in preeclamptic patients than in control subjects (OR=2.118, 95% CI=1.330-3.371, p<0.001).Conclusions: Our results suggest that GAS6 c.834+7G>A polymorphism may have a pivotal role in the pathogenesis of PE suggesting that the A allele has a protective role for PE.
Keywords: GAS6 polymorphism; inflammation; preeclampsia; KINASE RECEPTOR AXL; ENDOTHELIAL-CELLS; PLASMA-CONCENTRATIONS; SMOOTH-MUSCLE; PROTEIN; INFLAMMATION; EXPRESSION